A pilot study of the efficacy and safety of empiric daptomycin therapy in oncology patients with fever and severe neutropenia. (December 2013) - Bubalo, Joseph S.; Kullar, Ravina; Maziarz, Richard T.
Objectives: Patients with extended periods of time spent with low or absent absolute neutrophil counts (ANCs) are at risk for bacterial infections. Febrile neutropenia is a complication in this patient population, requiring administration of antibiotics. The use of daptomycin in treating patients with febrile neutropenia is not well described. Our objective was to describe the clinical course of febrile neutropenic patients that received daptomycin therapy. Methods: This was an open-labeled, pilot study of 30 patients with documented febrile neutropenia treated with empiric daptomycin. Eligible patients received daptomycin 6 mg/kg/day, in addition to concomitant broad-spectrum antimicrobials. The Kaplan–Meier method was used to estimate the median days to reach an afebrile state and negative bacterial cultures. Results: A total of 30 febrile neutropenic patients were enrolled and received daptomycin as part of an empiric antimicrobial regimen. All patients had severe neutropenia with ANC <100 cells/mm 3 . Two patients were removed from study due to the development of pneumonia. Clinically, 87% patients improved on daptomycin in combination with Gram-negative coverage, with 73% of patients succeeding therapy. A total of 18 of 19 (95%) subjects with positive blood cultures had microbiological eradication, with the median time to reach an afebrile state of 4.3 days (range 1–13). Four patients were discontinued from daptomycin due to a suspected related adverse event or to clinical failure. Conclusions: This pilot study supports future evaluation of the use of empiric daptomycin therapy in combination with Gram-negative coverage compared with vancomycin in patients with neutropenic fever in a large, randomized controlled trial.